Comparison of Sevoflurane Plus Dexmedetomidine Infusion and Dexmedetomidine Infusion to Prevent Awareness During Cardiopulmonary Bypass Surgery - Adnan Akram, Muhammad; Alam, Waqas; Masroor, Rehan; Raza Ali Shah, Syed Ali; Bashir Malik, Imran; Ali Memon, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find out the frequency of intra-operative awareness and to compare the effect of Sevoflurane plus Dexmedetomidine with only Dexmedetomidine infusion in preventing awareness during cardiopulmonary bypass surgery.Study Design: Quasi-experimental study.Place and Duration of Study: Adult Cardiac Surgery and Anesthesiology department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from May to Nov 2023.Methodology: Eighty patients who underwent elective cardiac surgery (valvular and CABG) on Cardiopulmonary Bypass  under general anesthesia irrespective of age and gender were recruited through non-probability consecutive sampling with non-random allocation of study participants. Patients were divided into S Group (Sevoflurane plus Dexmedetomidine Group) and D Group (Dexmedetomidine Group). Modified Brice questionnaire was used to assess awareness after 24 hours of surgery. Chi-square and t-test were applied to compare the study variables among study groups. p